2017
DOI: 10.1071/rd16232
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hyaluronan on endometrial receptivity and embryo attachment in sheep

Abstract: (200 words for RFD)An increasing number of reports suggests a role of hyaluronan (HA) in female reproduction and interest in its application in assisted reproduction is rising. However, there are contrasting data about the effectiveness of adding HA to the embryo-transfer medium on improving pregnancy rates. Using sheep as an experimental model, the studies reported here analysed the impact of HA infusion into the uterus on embryo attachment to uterine luminal epithelium (LE) and expression of selected mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The positive relation between HA and ER in this study agree with (9) who found that ER improve in ICSI cycle when HA pessaries used vaginally. Our finding disagrees with (10) .…”
Section: Discussioncontrasting
confidence: 99%
“…The positive relation between HA and ER in this study agree with (9) who found that ER improve in ICSI cycle when HA pessaries used vaginally. Our finding disagrees with (10) .…”
Section: Discussioncontrasting
confidence: 99%
“…Despite these studies indicating beneficial roles of HA in embryo development, many other studies have failed to find a positive influence of HA inclusion in embryo transfer media on pregnancy rate [102], [111]. The result of a recent study clearly demonstrated the need for HA clearance at the foetal-maternal interface in sheep for successful implantation to occur [112]. More studies are required to clarify this ambiguity on the role of HA inclusion in embryo transfer media and implantation.…”
Section: Hyaluronan Systemmentioning
confidence: 99%
“…HYAL-2 is also expressed in trophoblast giant binucleate cells and the multinucleated syncytia of sheep placentomes commencing on day 16 of gestation (Dunlap et al 2005), coinciding with the attachment and perhaps contributing to the clearance of HA at the implantation sites. In line with these reports, inhibition of HA by the infusion of 4-MU into the sheep uterus on day 14 after natural mating enhanced embryo implantation (Marei et al 2016b). Therefore, further prospective randomised clinical trials are essential for a robust conclusion to be made concerning the potential beneficial effects of HA pathway manipulation for women undergoing embryo transfer (Loutradi et al 2008).…”
Section: Embryo Implantation-contrasting Datamentioning
confidence: 82%